Effectiveness of a Counseling Package Based on Preventing Academic Procrastination on Learning Behaviors and Its Components - Karevan Brojerdi, Kiyana; Shariat Bagheri, Mohammad Mahdi; Salehi, Keyvan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Academic procrastination is a common problem that negatively impacts students’ academic performance and overall life. This study aimed to evaluate the effectiveness of a counseling package based on students’ lived experiences in preventing academic procrastination and its effect on improving learning behaviors and their components among female middle school students. Methods and Materials: This quasi-experimental study employed a pre-test, post-test, and follow-up design with a control group. The sample consisted of 60 female middle school students from Tehran, equally divided into experimental and control groups. The intervention included 12 counseling sessions lasting 60-90 minutes, focusing on various aspects of behavior, cognition, communication, motivation, and emotion. Data were collected using a standardized scale for learning behaviors and analyzed using SPSS version 26 with descriptive statistics and repeated measures ANOVA. Findings: ANOVA results showed significant improvement in the experimental group compared to the control group (p < 0.01). The Bonferroni post-hoc test indicated an increase in learning behaviors and their components in the post-test (p < 0.01), with effects persisting in the follow-up (p < 0.05). Conclusion: The counseling package based on students’ lived experiences effectively improves learning behaviors and their components. This approach can be integrated into educational programs to support students in overcoming procrastination and achieving better academic performance and improved mental health.